'I just find it boring': Findings from an affective adolescent reading intervention. Issue 1 (February 2017) - Cockroft, Charlotte; Atkinson, Cathy
Abstract : Research suggests that reading engagement and motivation are strong predictors of reading performance. Reading motivation may decline as students approach adolescence, resulting in less time spent with text. To date, there has been no research on how practitioners might directly support students to address affective factors in reading. In this exploratory case study, three disengaged, Year 8 readers received five sessions of an affective intervention aimed at helping them explore and challenge their own ambivalence towards reading. Quantitative and qualitative data from pre‐, post‐ and three‐month follow‐up indicated a range of benefits in relation to reading engagement and motivation, including improved self‐efficacy, increased participation and the usefulness of talking about affective factors in reading. Findings are further examined and implications for practitioners are discussed.